Accurate and computationally efficient nonlinear static and dynamic analysis of reinforced concrete structures considering damage factors. (1st January 2019) - Mourlas, Christos; Markou, George; Papadrakakis, Manolis
Highlights: 3D detailed modelling of reinforced concrete structures. Introduction of damage factors accounting the crack opening/closure effect. New material algorithm for concrete under cyclic and dynamic loading conditions. Validation is performed by comparing the numerical results with experimental data. Computational efficiency and robustness of the proposed algorithm are presented. Abstract: Accurate nonlinear dynamic analysis of reinforced concrete structures is necessary for estimating the behavior of concrete structures during an earthquake. A realistic modeling approach to assess their strength and their ability to carry the expected seismic forces is of great importance. Although a number of constitutive models and modeling approaches have been proposed in order to capture the behavior of reinforced concrete structures under static loading conditions, only a few of these numerical models have been extended to dynamic problems. The objective of this paper is to integrate a computationally efficient 3D detailed modelling of concrete structures with damage factors that take into account the opening and closing of cracks, as well as, damage factors for steel reinforcement considering the surrounding concrete damage level, in order to capture the level of damage and stiffness degradation of structures undergoing many loading cycles. In the adopted numerical model, the concrete domain is discretized with 8-noded isoparametric hexahedral finite elements, which treat cracking with the smeared crack approach, while the steel reinforcement is modeled as embedded beam elements inside the hexahedral mesh. The validity of the proposed method is demonstrated by comparing the numerical response with the corresponding experimental results of various reinforced concrete structural members and structures. Based on the numerical investigation, it was found that the proposed integration of the damage factors with computationally efficient concrete and steel material models can efficiently predict both static and dynamic nonlinear behavior of concrete structures, with the ability to capture the complicated phenomenon of the pinching effect.